Potensi Tenaga Kerja Perempuan Dalam Menyongsong Era Bonus Demografi. (Analisis Data Sakernas Agustus 2016) - Sapto Setyodhono (Jurnal Ketenagakerjaan, 2017)
Demographic Bonus is a condition of age structure with low dependency level and it is expected to occur in Indonesia in 2020-2030. Its need to be anticipated and put to good use. One way that can be done by preparing labor, especially female labor. This research aims to know the potency of female labor, related to the female labor force participation rate, unemployment rate, and who have experienced work in the last year but stopworking now according to education, age group and residence (urban and rural). Data used in this research is Sakernas (August 2016). Analysis used in this reseach is deskriptif analysis. The research show that the number of female labor is greater than men, but the labor force participation rate is lower. However, the unemployment rate is better. The low level of female labor force participation rate occur in urban, low education level and notin the productive age. High famale unemployment rate occur in rural, young age, and high school educated. Those whose work experinced stop workings largely out from labor market and taking care of household. In order to optimize the potency, it is necessary to expand the employment opportunities, improvement of education and training, enterpreneurship development, and agricultural business development in rural areas. In addition, it is necessary to extend the maternity leave policy for female worker, the provision of daycare facilities in the workplace as well as the obligation for housing developers to provide special building facilities for daycare.